The Effect of Bariatric Surgery on the Spectrum of Fatty Liver Disease - Jordan J. Nostedt; Noah J. Switzer; Richdeep S. Gill; Jerry Dang; Daniel W. Birch; Christopher de Gara; Robert J. Bailey; Shahzeer Karmali (Canadian Journal of Gastroenterology and Hepatology)
Nonalcoholic fatty liver disease is becoming one of the most common causes of liver disease in the western world. The most significant risk factors are obesity and the metabolic syndrome for which bariatric surgery has been shown to be an effective treatment. However, the effects of bariatric surgery on nonalcoholic fatty liver disease, specifically liver fibrosis and cirrhosis, are not well established. We review published bariatric surgery outcomes with respect to nonalcoholic liver disease. On the basis of this review we suggest that bariatric surgery may provide a viable treatment option for the treatment of nonalcoholic fatty liver disease, including patients with fibrosis and compensated cirrhosis, and that this topic should be a target of future investigation.